2021
DOI: 10.1111/jonm.13413
|View full text |Cite
|
Sign up to set email alerts
|

Progress and challenges for advanced practice nursing in Mexico and the United Kingdom

Abstract: Aim The aim of this study is to compare the advanced practice nursing development in Mexico with the United Kingdom. Background In spite of the involvement of global and local bodies to establish and develop advanced practice nursing worldwide, progress remains variable due to the lack of homogeneity in health care systems and policies. Evaluation Using thematic analysis from interviews of 29 health care professionals in Mexico, we identified four major issues that impact on the development of advanced practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(30 reference statements)
0
6
0
1
Order By: Relevance
“…La falta de una planificación adecuada al aplicar una nueva estrategia, o no incluir a los involucrados puede generar mayor desgaste en el capital humano (28). Para reducir esta barrera, es importante, en principio, desarrollar un modelo regulatorio de la ampliación de funciones de enfermería independiente del sistema de salud en el que se inserte, como se ha propuesto en publicaciones recientes (4,29). Además, es importante entender cómo funcionan los equipos y considerar estos factores al planificar la ampliación de los roles e impartir un programa educativo acorde a la normativa y a la experiencia de los participantes con el fin de mejorar la calidad del trabajo en equipo (30).…”
Section: Discussionunclassified
“…La falta de una planificación adecuada al aplicar una nueva estrategia, o no incluir a los involucrados puede generar mayor desgaste en el capital humano (28). Para reducir esta barrera, es importante, en principio, desarrollar un modelo regulatorio de la ampliación de funciones de enfermería independiente del sistema de salud en el que se inserte, como se ha propuesto en publicaciones recientes (4,29). Además, es importante entender cómo funcionan los equipos y considerar estos factores al planificar la ampliación de los roles e impartir un programa educativo acorde a la normativa y a la experiencia de los participantes con el fin de mejorar la calidad del trabajo en equipo (30).…”
Section: Discussionunclassified
“…Findings of a study of role satisfaction, highlighted that empowerment-related factors were also critical, including collegiality, professional growth and research [17]. Other studies have identifed the importance of organisational readiness and policies, governance and future planning in relation to succession and regulation [1,9,18,19]. An understanding of such factors is pivotal to the success of the ANP role and the redress of healthcare needs if sustainable change is to be achieved [14,20].…”
Section: Background and Contextmentioning
confidence: 99%
“…As part of the Better Health Programme, a gap analysis and thematic research were undertaken to identify the facilitators and barriers to advanced practice nurse development in Mexico ( Nigenda et al, 2021 ). Four major issues were identified that impact the development of advanced practice nursing: (a) workforce, (b) organizational and institutional, (c) regulatory and legal, (d) academic and educational.…”
Section: Global Future Trends Of Nursing and The Role Of The Regulato...mentioning
confidence: 99%
“…It is clear that further work needs to be done in both locations to expand and develop advanced practice nursing in a way that is consistent, productive, uniformly understood, and safe for the public and professionals. The gap analysis report undertaken as part of the Better Health Programme identified clear challenges for the education, training, and practice of nursing in Mexico and the United Kingdom, and it highlighted the need for stakeholders to reach key agreements to establish rigorous frameworks to support the development of advanced practice nursing in both settings ( Nigenda et al, 2021 ).…”
Section: Shared Learnings For the Nursing Regulatory Framework In Mex...mentioning
confidence: 99%
See 1 more Smart Citation